Leslie Marsh interviewed by Desley Reid for the Australia 1938 oral history project - Marsh, Leslie, 1902-; Reid, Desley; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1983)
Marsh speaks of his family background; father's business as a butcher; childhood memories; school memories; employment experiences as a clerk and a butcher; family life in Kew, Melbourne; family home; marriage and lifestyle after marriage.
Transcript unavailable.
Original and working duplicate cassettes made.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Keywords: Marsh, Leslie, -- 1902- -- Interviews; Kew (Vic.) -- Social conditions